Il principio di identità tra Heidegger ed Eraclito - Lanzirotti, Giulia (Scenari, 2024)
By considering the works of Heidegger and Heraclitus, this paper aims to offer a new reading of the principle of identity. I will discuss how the traditional expression of the law of identity A=A can be thought of as a reductive formulation of the experience of identity. I will argue that the principle of identity can be seen as a dynamic principle that can be recognised as the result of a synthetic inner movement. Therefore, I will attempt to combine a) early Heidegger’s ontology construed on the basis of modality; b) an interpretation of Heraclitus’ fragment 103 and of the notion of ξυνόν; and c) Heidegger’s analysis of the principle of identity. By means of these conceptual steps, it will be possible to discover that the formula “A is A” conceals a rather complex content, which allows us to consider identity as the synthetic result of a dynamic experience.